2020
DOI: 10.12973/eu-jer.9.4.1393
|View full text |Cite
|
Sign up to set email alerts
|

College English Language Teaching Reform and Key Factors Determining EFL Teachers’ Professional Development

Abstract: Owing to the rapid expansion and development of newly upgraded undergraduate colleges and universities in China, the Ministry of Education implemented the College English Language Teaching Reform (CELTR) to improve College English language teaching and learning at higher institutions. This reform aims to improve the quality of teaching and learning of English as a Foreign Language (EFL). The present study aims to identify potential factors influencing the EFL teachers' professional development in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Countries like Malaysia and Thailand teach soft skills in a conceptual, structured manner, and have curricula or technical guidelines for prospective teachers and teachers (Attakorn et al, 2014;Rozimela, 2020). Meanwhile, in China, the potential factors that influence the professional development of teachers, especially EFL teachers, are teacher understanding, self-reflection, and teaching practice (Zhiyong et al, 2020). PPG programs in Indonesia vary; teaching soft skills are not specifically given in a structured manner, but are taught and practiced at every learning opportunity or integrated .…”
Section: Discussionmentioning
confidence: 99%
“…Countries like Malaysia and Thailand teach soft skills in a conceptual, structured manner, and have curricula or technical guidelines for prospective teachers and teachers (Attakorn et al, 2014;Rozimela, 2020). Meanwhile, in China, the potential factors that influence the professional development of teachers, especially EFL teachers, are teacher understanding, self-reflection, and teaching practice (Zhiyong et al, 2020). PPG programs in Indonesia vary; teaching soft skills are not specifically given in a structured manner, but are taught and practiced at every learning opportunity or integrated .…”
Section: Discussionmentioning
confidence: 99%
“…At present, college English teaching in medical colleges is being carried out in an orderly manner [10]. Literature [11] according to the present situation of English teaching in China, it is proposed that English teaching in universities, primary and secondary schools should form systematic planning and management in the aspects of the syllabus, textbook selection, and test evaluation so as to change the long-standing problems in English teaching in China, such as time-consuming and inefficient, improper selection of textbooks, disjointed connection of different stages, and so on.…”
Section: Related Workmentioning
confidence: 99%
“…It implements the improvement of the teaching process in ELT. It improves the quality of learning and teaching of English Foreign Language or English Language that influence the participation of the professional teacher's development in the college context of the English Language Teaching curriculum (Zhiyong, Muthukrishnan, & Sidhu, 2020). Generally, the participants observed that:…”
Section: Participationmentioning
confidence: 99%